A Commercial Arbuscular Mycorrhizal Inoculum Alleviated the Effects of Acid Water on Lupinus angustifolius Grown in a Sterilized Mining Dump - Aurora Neagoe; Virgil Iordache (Plants, 2023)
Lupinus species have been sporadically reported to be colonized by arbuscular mycorrhizal fungi (AMF). The interactions between AMF and lupine plants could also be non-symbiotic, from positive to negative, as controlled by the stress conditions of the plant. The goal of the study was to reveal the existence of such positive interactions and provide preliminary data for a myco-phytoremediation technology of mining dumps using L. angustifolius as a first crop. The objective was to test the hypothesis that the AMF inoculation of an acidified dump material contaminated with heavy metals would improve the growth of L. angustifolius and decrease oxidative stress. The design consisted of a one-month bivariate pot experiment with plants grown in a mining dump soil inoculated and not inoculated with a commercial AMF inoculum sequestered in expanded clay and watered with acidic and neutral water. There was no AMF root colonization under the experimental conditions, but under neutral and acidic water conditions, the phosphorus concentrations in roots and leaves increased, and the superoxide dismutase and peroxidase activities significantly decreased due to AMF inoculation. The increase in leaf phosphorus concentration was correlated with the decrease in peroxidase activity. The fresh weight of shoots and leaves significantly increased due to the commercial inoculum (under acidic water conditions). At the end of the experiment, the ammonium concentration in the substrate was higher in the inoculated treatments than in the not inoculated ones, and the concentrations of many elements in the dump material decreased compared to the start of the experiment. A comprehensive discussion of the potential mechanisms underlying the effects of the commercial AMF inoculum on the non-host L. angustifolius is completed.